2018
DOI: 10.7759/cureus.2364
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity and Thyroid Cancer at a Tertiary Care Hospital in Pakistan

Abstract: ObjectiveThyroid cancer (TC) is one of the most common endocrine malignancies with a rapidly increasing worldwide presence. In Pakistan, it is more prevalent in females than males and has an incidence rate of 2.1%. Obesity and excess body mass index (BMI) has been linked to several cancers and is thought to be a risk factor for TC. We aim to investigate the incidence of TC in our population and understand it’s correlation with obesity.SubjectsThe study was a retrospective case series conducted in the years 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In Pakistan, some hospitals report diagnosed thyroid cancer cases; from that, the evidence of an increasing trend of thyroid cancer can be established, 25,26 but the exact prevalence of thyroid cancer is difficult to assess due to the lack of population-based statistics. Future information on the geographical distribution of cancer secondary to the detection of cancer in preventive screening relative to indigenous iodine sources will be of great value for the generation of epidemiologic hypothesis and formulation of concepts for the etiology of thyroid cancer increased prevalence in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pakistan, some hospitals report diagnosed thyroid cancer cases; from that, the evidence of an increasing trend of thyroid cancer can be established, 25,26 but the exact prevalence of thyroid cancer is difficult to assess due to the lack of population-based statistics. Future information on the geographical distribution of cancer secondary to the detection of cancer in preventive screening relative to indigenous iodine sources will be of great value for the generation of epidemiologic hypothesis and formulation of concepts for the etiology of thyroid cancer increased prevalence in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Future information on the geographical distribution of cancer secondary to the detection of cancer in preventive screening relative to indigenous iodine sources will be of great value for the generation of epidemiologic hypothesis and formulation of concepts for the etiology of thyroid cancer increased prevalence in Pakistan. Additionally, the increasing incidence of thyroid cancer cases in the Pakistani population 25 could be due to unawareness of this dreadful disease and other contributing factors such as genetic, familial history, diet, radiation, and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies have suggested that gender is a vital factor that effects the relationship between obesity and thyroid cancer [105][106][107][108]. Several studies have shown that obesity increases the risk of thyroid cancer regardless of gender or only in men [109], whereas the majority of population-based studies indicate that obesity increases the risk of thyroid cancer in women [110][111][112]. Additionally, BMI seems to be significantly affected by age.…”
Section: Research Progress On Obesity and Thyroid Cancermentioning
confidence: 99%
“…Additionally, BMI seems to be significantly affected by age. A study in Pakistan showed that although patients with thyroid cancer were mostly obese women, obese patients > 45 years of age accounted for 72.8% of all patients [ 110 ]. A recent study conducted by He et al [ 101 ] suggested that an increased BMI value is accompanied by a risk for DTC in women of all ages and men under 50 years old, but not in men over the age of 50.…”
Section: Obesity and Thyroid Cancermentioning
confidence: 99%
“…The incidence of obesity‐related thyroid carcinoma (TC) has increased rapidly in the past few decades in different regions of the world, such as East Asia, 1 West Asia, 2 South Asia, 3 Eastern Oceania, 4 America, Europe, and the Mediterranean, 5 particularly papillary TC, and the increasing incidence of TC may be at least partly attributed to excess body fatness 6 . Although most TCs are generally asymptomatic and slow‐growing and patients with TC have a better life expectancy, overall mortality rates and advanced‐stage cases for TC may be a true rise 7 .…”
Section: Introductionmentioning
confidence: 99%